2021
DOI: 10.1159/000516444
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Sex-Determining Region Y-Box 2 and CD8+ Tumor-Infiltrating Lymphocytes in Limited-Stage Small-Cell Lung Cancer

Abstract: <b><i>Background:</i></b> Sex-determining region Y-box 2 (SOX2) is a transcriptional factor that drives embryonic stem cells to neuroendocrine cells in lung development and is highly expressed in small-cell lung cancer (SCLC). However, the prognostic role of SOX2 and its relationship with tumor-infiltrating lymphocytes (TILs) has not been determined in SCLC. Herein, we assessed the expression of SOX2 and CD8+ TILs to obtain insights into the prognostic role of SOX2 and CD8+ TILs in limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Expression of SOX2 in cells that cause ovarian serous tumor spread allows tumors to withstand conventional chemotherapy and enhances their tumorigenicity77 However, a study by Le et al on small cell lung carcinoma that did not differentiate between intratumoral and stromal TILs found that high SOX2 and CD8+ TIL expression indicated high overall survival (OS) and progression free survival (PFS). 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of SOX2 in cells that cause ovarian serous tumor spread allows tumors to withstand conventional chemotherapy and enhances their tumorigenicity77 However, a study by Le et al on small cell lung carcinoma that did not differentiate between intratumoral and stromal TILs found that high SOX2 and CD8+ TIL expression indicated high overall survival (OS) and progression free survival (PFS). 24…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, high SOX2 expression in SCLC was significantly associated with poor prognosis. 14 Tumor Infiltrating Lymphocytes (TILs)consists of a heterogeneous collection of lymphoid cells that exhibit diverse antitumor activity and spatial distribution, characterized by the expression of several molecular biomarkers such as CD8, CD3, CD4, CD103 and PD-1. 15 Accumulation of TILs in ovarian cancer is prognostic for increased survival while increasingimmunosuppressive regulatory T cells (Tregs)associated with poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors and components of the tumor microenvironment, including neoangiogenesis and the status of tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs) related to tumor immunity, have been reported to play important roles in the clinical and/or biological behavior of cancer cases [14][15][16][17][18][19][20]. For example, the increased infiltration of CD8-positive lymphocytes into tumor tissues was reported to be associated with better clinical outcome of the patients, whereas that of CD4and Foxp3-positive lymphocytes with their worse prognosis [21][22][23][24][25][26][27]. da Silva et al also reported no significant differences in the intra-tumoral CD3-and CD8-positive lymphocyte infiltration status between gastrointestinal and pancreatic NETs [25].…”
Section: Introductionmentioning
confidence: 99%